Is non-invasive ventilation effective in improving the exercise capacity in patients with cardiac heart failure?: A randomised crossover trial - Guillermo Mazzucco; Rodrigo Torres-Castro; Leonardo Intelangelo; Ana Lista-Paz; Juan Pablo Escalante; Lore Zumeta-Olaskoaga; Gonzalo Veiga; Ane Arbillaga Etxarri (PLoS ONE, 2025)
Introduction Heart failure (HF) is a prevalent global health issue, characterized by the heart’s inability to effectively pump or fill with blood, leading to inadequate cardiac output. Despite advances in medical treatments, exercise intolerance remains a significant challenge, impacting their quality of life and contributing to frequent hospitalizations. Recent studies suggest that non-invasive ventilation (NIV) may further enhance exercise performance by reducing ventilatory workload and fatigue. However, limited research has directly compared different ventilatory modes during exercise in patients with heart failure. This study aims to evaluate the effects of two NIV devices on exercise capacity. Methods A randomised crossover trial was conducted in patients with HF, reduced ejection fraction (≤ 40%), New York Heart Association functional class I-III and clinically stable. All participants underwent an initial assessment followed by an incremental exercise test to determine maximum aerobic velocity. They were then randomized to perform three constant work rate tests on separate days under three conditions: (1) with Continuous Positive Airway Pressure (CPAP), (2) with pressure support (PS) and (3) without NIV. The primary outcome was time to exhaustion. Key physiological variables were recorded during each test. Participants were recruited and completed all testing between April 29 and July 18, 2022. ClinicalTrials.gov registration number: NCT05433610. Results A total of 11 patients (mean age: 67 ± 9.6 years) completed the study. Exercise duration was significantly longer in the pressure support group (9.8 ± 6.2 minutes) compared to the CPAP group (8.9 ± 6.0 minutes) and the control group (7.3 ± 6.2 minutes) (p = 0.043). No significant differences were found in average heart rate (HR), final HR, or oxygen saturation (SpO₂) between the groups (p > 0.05). Similarly, dyspnea and leg fatigue (modified Borg scale) showed no statistically significant differences between conditions (p > 0.05). Conclusion The use of NIV, particularly the PS mode, during exercise significantly improved exercise duration in patients with HF compared to CPAP or no ventilatory support. Clinical Trial Registration ClinicalTrials.gov Identifier: NCT05433610